1966
DOI: 10.1002/aja.1001180306
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the face and jaws after resection of the septal cartilage in the rabbit

Abstract: Varying amounts of the cartilaginous nasal septum were resected in 15 growing rabbits at 21 days of age. Ten additional rabbits were used as unoperated on and operated on controls. The postoperative survival ranged from 105 to 145 days.Within 60 to 90 days postoperatively, antemortem findings were noted in the experimental animals of a shorter snout and overeruption and malocclusion of the incisors. Postmortem gross findings of the dissected, sectioned and x-rayed skulls of the experimental animals revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
1

Year Published

1968
1968
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(59 citation statements)
references
References 11 publications
2
56
0
1
Order By: Relevance
“…The results of our analysis indicate that the developmental relationship between the nasal septum and premaxilla, as one component of midfacial growth, contributes to variation in adult facial length (e.g., Wexler and Sarnat, 1961;Sarnat and Wexler, 1966;Mooney et al, 1989;Wealthall and Herring, 2006). Our first hypothesis that facial growth restriction has no effect on the length of the nasal septum was indirectly supported by this analysis.…”
Section: Discussionsupporting
confidence: 61%
“…The results of our analysis indicate that the developmental relationship between the nasal septum and premaxilla, as one component of midfacial growth, contributes to variation in adult facial length (e.g., Wexler and Sarnat, 1961;Sarnat and Wexler, 1966;Mooney et al, 1989;Wealthall and Herring, 2006). Our first hypothesis that facial growth restriction has no effect on the length of the nasal septum was indirectly supported by this analysis.…”
Section: Discussionsupporting
confidence: 61%
“…The spreading of the bones connected by a suture is, in Scott's view, due to extra-sutural influences, for instance the growing brain, the eyeballs, and the growing cartilage of the basal synchondroses and nasal septum.The cartilaginous structures, in particular,are considered important by this investigator. Thus he sees the cartilaginous nasal septum as a chief factor in the growth of the maxilla, a view shared by Sarnat and Wexler (1966). As regards the significance of the condylar cartilage for the growth of the mandible, here Scott agrees with Weinmann and Sicher, and the other workers mentioned.…”
Section: в Theories Of the Mechanism Of Cranial Growthsupporting
confidence: 77%
“…Most extirpation experiments have shown that removal of all or part of the septal cartilage reduces facial growth, especially in the rostrocaudal direction, or lengthening of the snout (Sarnat and Wexler, 1966;Kvinnsland and Breistein, 1973). However, some extirpation experiments have shown no significant facial growth reductions (Stenstrom and Thilander, 1970;Cupero et al, 2001).…”
mentioning
confidence: 99%